FRI0393 Prevalence of myositis-specific antibodies in idiopathic inflammatory myopathy compared to disease and healthy controls. (15th June 2017) - Vulsteke, J-B; Bossuyt, X; Dillaerts, D; Poesen, K; Claeys, K; Lenaerts, J; Westhovens, R; Blockmans, D; Haes, P De; Langhe, E De
Abstract : Background: Myositis-specific autoantibodies (MSA) are increasingly recognized as important diagnostic and prognostic markers in idiopathic inflammatory myopathies (IIM) (polymyositis, dermatomyositis, sporadic inclusion body myositis and necrotizing autoimmune myositis). The prevalence of these MSAs in other systemic autoimmune rheumatic diseases and neuromuscular diseases is unclear. Objectives: To compare positivity of MSA in a cohort of IIM patients to positivity in healthy controls and different systemic autoimmune rheumatic diseases (SARD) or chronic inflammatory demyelinating polyneuropathy (CIDP). Methods: A line immunoassay (Myositis 12 IgG DOT for BlueDiver) for IgG autoantibodies against Jo-1, PL-7, PL-12, EJ, SRP, Mi-2, MDA-5, TIF1-γ, HMGCR, SSA/Ro52kD, SAE1/2 and NXP-2 antigens was performed in patients with IIM (n=146), healthy controls (blood donors, n=40) and disease controls (n=200). The disease control group consisted of patients with other SARD (rheumatoid arthritis, RA; systemic sclerosis, Ssc; Sjögren's syndrome, SjS; and systemic lupus erythematosus, SLE) (n=40 for each disease group) and CIDP (n=40). A result >10 arbitrary units was considered significantly positive. Results: 50% of 146 patients with IIM tested positive for an MSA (table 1 ), compared to 3, 5% of 200 disease controls (table 1 ). 1 SSc patient was positive for Jo-1, 1 CIDP patient was positive for PL12, 2 SSc patients were positive for TIF1-gamma, 2 patients (1 SSc and 1 SjS patient) were positive for SAE1/2, and 1 SjS patient was positive for NXP2. The prevalence of SAE1/2 and TIF1-gamma positivity was similar in the IIM and disease control group. No healthy control had a significantly positive MSA. Conclusions: MSA positivity in patients with a clinical non-IIM diagnosis (other SARD or CIDP) is infrequent compared to positivity in the IIM group. For TIF1-gamma and SAE1/2 assay performance may need to be optimized. The distribution of subtypes of MSA in this IIM cohort is consistent with data of previous studies. 1 References: Allenbach Y, Benveniste O. Diagnostic Utility of Autoantibodies in Inflammatory Muscle Diseases. J Neuromuscul Dis. 2015; 2:13–25. Disclosure of Interest: None declared